Mass Media as a Tool for Promotion of Girl-Child Education in Zaria Metropolis, Kaduna State - Garba, Ishaq (POMLIF Journal of Library and Information Science, 2021)
The study assesses the role of the media in the promotion of girl-child in Zaria metropolis. The survey research method was adopted, using questionnaires as an instrument to elicit information from the respondents. Findings from the analysis of the data gathered show that several factors act as hindrances to girl-child education in Zaria metropolis. Such factors among others include: poverty, sexual violence, sexual abuse, culture and religion. Findings further revealed that girl-child education is poor in Zaria Metropolitan Local Government Areas. More so, findings show that the media have been used to promote girl-child education in Zaria Metropolis, but the extent to which they are used is minimal. Based on the above findings, the paper concludes that girl-child education is not given due recognition in Zaria Metropolitan Local Government Area and that the media, which are the agents of social change, have not fared well in creating awareness about girl-child education and that the extent to which girl-child education is embraced in Zaria Metropolitan Local Government Area is poor.